Գրիգոր Նազիանզացու ուսմունքը՝ Սուրբ Հոգու աստուածութեան մասին - Ծաղիկեան, Դիանա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлен огромный вклад Григория Назианзина в формировании учения о Божестве Святого Духа и в деле окончательного формулирования учения о св. Троице. Анализируя учение Григория Назианзина о Божестве Святого Духа, в частности в контексте 31-й проповеди, автор последовательно излагает и анализирует учение Назианзина о Божестве Святого Духа. Автор также представляет общие черты и особенности учения Назианзина в сравнении с другим известным каппадокийцем—Василием Великим. В статье подчеркивается мысль что по всей вероятности одним из самых интересных аспектов богословия было развитие и уточнение учения о св.Троице. Исследование может служить ценным учебным материалом для глубокого понимания Учения св. Григория Богослова о Божестве Святого Духа. The article presents the enormous contribution of Gregory of Nazianzus to the formation of the doctrine of the Deity of the Holy Spirit and to the final formulation of the Trinitarian doctrine. Analyzing the teaching of Gregory of Nazianzus on the Deity of the Holy Spirit, in particular in the context of the 31st sermon, the author consistently expounds and analyzes the teaching of Gregory of Nazianzus on the Deity of the Holy Spirit. The author also presents the general features and peculiarities of Gregory’s teachings in comparison with another famous Cappadocian father, Basil the Great. The article emphasizes the idea that, in all likelihood, one of the most interesting aspects of theology was the development and refinement of the Trinitarian doctrine. The study can serve as a valuable educational material for a deep understanding of the teachings of St. Gregory the Theologian on the Deity of the Holy Spirit.
Keywords: Կրօնագիտութիւն